ANALYSIS OF ISLAMIC FINANCIAL INSTITUTIONS ON POVERTY IN INDONESIA - Nufus, Shoufa Hayatun; Yazid, Muhammad (UIN Mataram, 2023)
Poverty is a complex problem and must be addressed immediately. Various efforts have beendesigned and realized by the government to reduce poverty in Indonesia. One of them isestablishing a financial institution that is based on Islamic principles commonly known as anIslamic Financial Institution (LKS). The purpose of this study is to find out the role of Islamicfinancial institutions in poverty alleviation. This research uses the library research method withthe search engine used in the literature search is Google Scholar with the keywords IslamicFinancial Institutions, poverty alleviation, and poverty of the Indonesian people. The results ofthe study show that in the LKS there are instruments that can help solve the problem of poverty,namely through the distribution of zakat, utilizing the insurance sector, the BMT program, andcapital development as an effort to alleviate poverty. The conclusions of this study indicate thatIslamic Financial Institutions can assist the poor in solving the problem of poverty. in povertyalleviation following the goals of the SDGs. Islamic financial institutions have a role, namelyhelping underprivileged communities by holding zakat distribution programs, utilizing theinsurance sector, increasing people's income and businesses to bring prosperity such as throughMSME funding, and being able to reduce poverty. to channel various funding needs so that itcan have positive value for economic improvement in society as a poverty alleviation effort inIndonesia.